Aging Changes and Exercises - Ratanajaratrote, Bunlue; Limnararat, Kornthip (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2023)
Thailand has recently focused on elderly persons. Thai society has become an aging society since 2021. The entering of the aging society effected rapid changes in their bodies that caused degenerative processes, lower performance, and slower decision-making. Moreover, this factor decreased confidence in performing daily activities as well. These changes affected the ability to maintain balance in the body and the fear of falling. The elderly often stayed only at home. They do not participate in social activities, leading to the effect on the economy. The pay for medical treatment, sickness, and various diseases is increasing. This article aimed to provide knowledge about changes in anatomy and physiology, social and economic, emotional and psychological aspects of elders. Because of increasing age, there is a tendency to change the functions of various systems in the body, which would cause illness. Most of the studies found that exercise could help to reduce the risk of diseases and increase the efficiency of both the circulatory and respiratory systems and the joint movements. Exercise could increase muscle strength, reduce falls, control the balance of the body, and have effective movement. Exercise could affect older people's ability to live independently and happily. It could create a better society and reduce the burden of dependency on elders in the future.